Self-confidence, competitive anxiety and predictors of free throw success - Vardo, E.; Pojskic, H. (Sport Science - International Scientific Journal of Kinesiology, 2014)
The goal set before this research is oriented towards determining the correlation between aspects of competitive anxiety and self-confidence with precision for making free throws in basketball. The Competitive State Anxiety Inventory-2; CSAI-2, Martens et al., 1990 was used on the sample of 55 basketball players from four clubs in BH (N=55). We examined the forms of anxiety (cognitive and somatic anxiety) and the level of self-confidence just before the game (30 minutes before the game). For the same subjects we took official club statistics with the emphasis on long range competitive precision shooting parameters (shooting percentage for one point during the season). Multiple regression analysis results for the examined sample indicate that the above mentioned variables (cognitive anxiety, somatic anxiety and self-confidence) are not significant predictors of success in competitive precision when making free throws in basketball. This result is somewhat in line with the findings of similar previous research.